(untitled) (Transport systems and technologies, 2018)
Current non-traction rolling stock is a complex system, the resource of which limits several basic elements (nodes). Normative documentation regulates the time and expenses for the diagnosing of rolling stock equipment, the time for replacement during preventive repair or failure, as well as cost of a separate node, which allows to estimate the costs of operation of the wagon for the entire period of its exploitation. Together with this, for complex substitutable nodes to determine the costs that depend on the spin after the next replacement of their worn parts is a difficult task. It is obvious that the time necessary for preventive replacements of similar parts of the resource will be less than the sum of time for an individual (permission) replacement and depends on the design and technological features of the site, details. In this regard, and loss of downtime repairs during preventive replacements will also decrease due to increasing the number of simultaneously replaceable details. The difference in costs for separate and prophylactic group replacements is a criterion for assessing the advisability of grouping replaceable elements. The greater the difference in such an organization of prevention, the higher the cost effectiveness of carrying out prophylactic replacements.